Fibroblast growth factor-21 is required for weight loss induced by the glucagon-like peptide-1 receptor agonist liraglutide in male mice fed high carbohydrate diets - Thao D.V. Le; Payam Fathi; Amanda B. Watters; Blair J. Ellis; Gai-Linn K. Besing; Nadejda Bozadjieva-Kramer; Misty B. Perez; Andrew I. Sullivan; Jesse P. Rose; Laurie L. Baggio; Jacqueline Koehler; Jennifer L. Brown; et al. (Elsevier, 2023)
Objective: Glucagon-like peptide-1 receptor (GLP-1R) agonists (GLP-1RA) and fibroblast growth factor-21 (FGF21) confer similar metabolic benefits. GLP-1RA induce FGF21, leading us to investigate mechanisms engaged by the GLP-1RA liraglutide to increase FGF21 levels and the metabolic relevance of liraglutide-induced FGF21. Methods: Circulating FGF21 levels were measured in fasted male C57BL/6J, neuronal GLP-1R knockout, β-cell GLP-1R knockout, and liver peroxisome proliferator-activated receptor alpha knockout mice treated acutely with liraglutide. To test the metabolic relevance of liver FGF21 in response to liraglutide, chow-fed control and liver Fgf21 knockout (LivFgf21−/−) mice were treated with vehicle or liraglutide in metabolic chambers. Body weight and composition, food intake, and energy expenditure were measured. Since FGF21 reduces carbohydrate intake, we measured body weight in mice fed matched diets with low- (LC) or high-carbohydrate (HC) content and in mice fed a high-fat, high-sugar (HFHS) diet. This was done in control and LivFgf21−/− mice and in mice lacking neuronal β-klotho (Klb) expression to disrupt brain FGF21 signaling. Results: Liraglutide increases FGF21 levels independently of decreased food intake via neuronal GLP-1R activation. Lack of liver Fgf21 expression confers resistance to liraglutide-induced weight loss due to attenuated reduction of food intake in chow-fed mice. Liraglutide-induced weight loss was impaired in LivFgf21−/− mice when fed HC and HFHS diets but not when fed a LC diet. Loss of neuronal Klb also attenuated liraglutide-induced weight loss in mice fed HC or HFHS diets. Conclusions: Our findings support a novel role for a GLP-1R-FGF21 axis in regulating body weight in a dietary carbohydrate-dependent manner.